Dispensing with Style - Small, H (Cambridge University Press, 2013)
‘I dispense with style’, M. Blandois/Rigaud tells Abel Flintwinch, with a Gallic wave of the hand (LD, i, 30, 345). He does and does not mean it. The lack of any stylistic attractions, any marks of fashion or elegance, about the Clennam house is irrelevant to Blandois’s purposes there, and no obstacle to pressing an entry; he is, at the same time and in his own person, an excrescence of style – a florid incursion of melodramatic mannerism into the mix of styles that constitutes and troubles Dickensian realism – one that must ultimately be ‘squashed’ (to borrow Garrett Stewart’s apposite verb) to permit a harmonious narrative conclusion for Little Dorrit. Critics standardly observe that Dickensian stylistic excess has a companion principle, a kind of counterweight in restraint or adherence to ‘limits’. It is a less obvious proposition that there might be, beyond this tension or contest between the unleashing and the control of expressive energy, and outside the specific acts of repression required for Dickens’s novels to conclude, any effort towards ‘plain style’. Applied across the whole career, the proposal would not (to invoke one of Dickens’s favoured objects of humour) have legs. But the first part of this essay tests the claim that, in so far as he had a worked-out theory of style (he had clear principles and gave consistent advice to others, but never spelled out a complete ‘theory’), he afforded a high place to Hazlitt’s definition of ‘plain style’. The virtues expressed in the idea of ‘plain style’ were at the heart of his sense of how good writing is to be distinguished from bad, and in many aspects of his writing he both abided by them himself and encouraged (or directed) others to do so.